B2SAPP: blockchain based solution for maritime security applications - Farao, Aristeidis; Zarras, Apostolis; Voudouris, Anastassis; Paparis, Georgios; Xenakis, Christos (Frontiers in Computer Science, 2025)
The digitization of the maritime industry is accelerating rapidly. However, critical infrastructures face greater cyber security risks as they become more interconnected. As digital technologies advance, so do the adversaries that exploit them. The threat posed by cyber criminals and state-sponsored actors is more significant than ever, and the shipping sector's central role in global supply chains makes it a prime target for cyberattacks. This article introduces B2SAPP, an innovative privacy-preserving framework designed to deliver robust security and privacy protections for maritime operations. By leveraging Hyperledger Aries and Hyperledger Fabric, B2SAPP provides reliable authorization of the entities involved in the maritime ecosystem, as well as secure storage for Vessel operational data. We have implemented the core components of B2SAPP and conducted a quantitative performance assessment, demonstrating its feasibility. We further validate its security and privacy attributes, confirming that B2SAPP meets its design objectives. In summary, B2SAPP represents a forward-thinking solution poised to enhance cyber insurance against evolving cyber threats, offering a promising avenue for safeguarding organizations and policyholders in the digital era.